Severe autoimmune hemolytic anemia following immunotherapy with checkpoint inhibitors in two patients with metastatic melanoma: a case report - Fetter, Tanja; Fietz, Simon; Bertlich, Maya; Braegelmann, Christine; de Vos-Hillebrand, Luka; Wenzel, Joerg; Heine, Annkristin; Landsberg, Jennifer; Jansen, Philipp (Frontiers in Immunology, 2024)
Introduction Over the past decade, immune checkpoint inhibitors such as antibodies against cytotoxicity T-lymphocyte-associated protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1) have become an important armamentarium against a broad spectrum of malignancies. However, these specific inhibitors can cause adverse autoimmune reactions by impairing self-tolerance. Hematologic side effects of immune checkpoint inhibitors, including autoimmune hemolytic anemia (AIHA), are rare but can be life-threatening. Case report Herein, we report two patients on immune checkpoint inhibitors for metastatic melanoma who developed AIHA with symptoms of dyspnea and fatigue. In the first patient, symptoms alleviated after discontinuation of combined anti CTLA-4 and anti-PD-1 therapy, initiation of corticosteroids and application of a single red blood cell transfusion. Due to subsequent progress of melanoma, combinational anti-PD-1 and tyrosine kinase inhibitor therapy was initiated based on multidisciplinary tumor board decision. After two months, she again developed the described hematological and clinical signs of AIHA leading to cessation of anti-PD-1 therapy and initiation of corticosteroids, which again resulted in an alleviation of her symptoms. Due to further progression, the patient received dacarbazine for several months before she decided to stop any therapy other than palliative supportive care. In the second patient, discontinuation of anti-PD-1 therapy and initiation of corticosteroids entailed a complete alleviation of his symptoms. After refusing chemotherapy due to subsequent melanoma progression, he received radiotherapy of bone metastases and is currently enrolled in a clinical trial. The patient did not develop AIHA ever since. Conclusion Hematologic immune-related adverse events due to treatment with immune checkpoint inhibitors are rare but can have life-threatening consequences. If dyspnea and other clinical symptoms are present, AIHA should be considered as a potential cause and treated promptly in a multidisciplinary setting. An expanded comprehension of risk factors and pathogenesis of AIHA is needed to identify high-risk patients beforehand, leading to more effective predictive and reactive treatment approaches.